Effects of Biochar on the Soil Carbon Cycle in Agroecosystems: An Promising Way to Increase the Carbon Pool in Dryland - Li, Mengying; Xiong, Youcai; Cai, Liqun (IOP conference series. Earth and environmental science, 2021)
Dryland agriculture ecosystems occupy an extremely important position in ensuring global food security. However, they have faced problems of low soil organic matter content and poor long-term soil sustainability. Biochar is regarded as a new means of soil remediation and a pathway of carbon sequestration that has improved the soil structure and function of ecosystems due to its complex physical and chemical properties. Since there are few reviews of biochar’s role in the carbon cycle of agricultural ecosystems, this article examines recent research about its influence on plant carbon assimilation, soil organic carbon mineralization and storage. We highlight the direct or potential effects of biochar on the relationships between plant root architecture and carbon storage, the soil priming effect and soil aggregation, to provide new perspectives on the study of its impacts on the carbon cycle and the implications for carbon management in dryland agriculture ecosystems.